Legal Liability of Former Bank Employees for Leakage of Bank Secrets - Utsman Mubarok, Muhammad (International Significance of Notary, 2023)
Abstract : Banks as essential institutions in the national financial system are very dependent on public trust in running their business entities. The public has trusted banks as intermediary institutions in managing and channeling customer finances through loans or credit. Thus, to maintain customer trust, a banking business entity has an obligation to maintain bank secrecy from unauthorized parties to avoid misuse. The problem in this study is the ambiguity of the obligation to maintain bank secrecy for former banking employees. The purpose of this study is to examine the liability of former banking employees in the event of a violation of the obligation to maintain bank secrecy. This study uses a normative research method with a statutory and conceptual approach. The results of the study show that former banking employees in Indoensia have no obligation to maintain bank secrecy because there are no regulations governing the obligation. Therefore, it is necessary to have regulations governing the obligation to maintain bank secrecy by former employees of banking business entities.Keywords : System Bank secrets, liability, banks, employees, customers, leaks